Cell adhesion and migration in disease: translational and therapeutic opportunities - Kurt Anderson; Yolanda Calle-Patino; Aleksandar Ivetic; Maddy Parsons; Ferran Valderrama; Claire Wells; Ines M. Anton (Cell Adhesion & Migration)
In September 2023 members of the cell adhesion and cell migration research community came together to share their latest research and consider how our work might be translated for clinical practice. Alongside invited speakers, selected speakers and poster presentations, the meeting also included a round table discussion of how we might overcome the challenges associated with research translation. This meeting report seeks to highlight the key outcomes of that discussion and spark interest in the cell adhesions and cell migration research community to cross the perceived valley of death and translate our work into therapeutic benefit.